The Fourth Trimester: Pregnancy as a Predictor of Cardiovascular Disease - Pensée Wu; Ki Park; Martha Gulati (European Cardiology Review, 2021)
Pregnancy identifies women who may be at a greater risk of cardiovascular disease (CVD), based on the development of adverse pregnancy outcomes (APOs), and may identify women who may benefit from atherosclerotic CVD (ASCVD) risk reduction efforts. APOs are common and although they are separate diagnoses, all these disorders seem to share an underlying pathogenesis. What is not clear is whether the APO itself initiates a pathway that results in CVD or whether the APO uncovers a woman’s predisposition to CVD. Regardless, APOs have immediate risks to maternal and foetal health, in addition to longer-term CVD consequences. CVD risk assessment and stratification in women remains complex and, historically, has underestimated risk, especially in young women. Further research is needed into the role of ASCVD risk assessment and the effect of aggressive ASCVD risk modification on CVD outcomes in women with a history of APOs.